Identification of silibinin and isotretinoin as potent up-regulators of sFRP4 (Wnt antagonist): In silico prediction and in vitro validation in breast cancer - Ramzan, Rehana; Bukhari, Shazia Anwer; Rasul, Azhar (PLOS ONE, 2025)
Secreted frizzled-related protein 4 (sFRP4) plays a fundamental role in the regulation of Wnt signalling, which is crucial for cellular proliferation and differentiation. The sFRP4 has garnered significant interest as a therapeutic target for metabolic diseases and cancer due to its mechanism of action. Although existing sFRP4 modulators show limited specificity and notable off-target effects, our study explores the potential of known bioactive compounds as more selective and less toxic alternatives. This study is based on the analysis of expression profiles, which demonstrated that the sFRP4 gene exhibits aberrant expression in multiple cancers, including breast cancer. The protein’s primary involvement in cancer signaling pathways was determined through pathway enrichment analysis. The study employed molecular docking analyses and MD simulations to identify breast cancer-fighting small molecules with docking energies of less than −6 kcal/mol, targeting the sFRP4 binding hotspot using 100 natural or synthetic small molecules. Out of 100 screened compounds, Silibinin and Isotretinoin were selected based on docking results and further validated in vitro. In vitro investigations were carried out using the colorimetric MTT assay to assess cell viability and cytotoxicity based on metabolic activity. The potential of Silibinin and isotretinoin to upregulate the tumour suppressor sFRP4 was further examined using ELISA and real-time quantitative PCR. Our study identified potential compounds for high-potential drug candidates against sFRP4, demonstrating their effectiveness in cancer cell death and upregulating sFRP4 expression through improved drug design methods and experimental studies. In conclusion, our in-silico findings could facilitate the discovery of potential therapeutic agents against breast cancer. Silibinin and Isotretinoin impede cancer cell development in vitro; nonetheless, this study demonstrated that they directly upregulate sFRP4 and induce apoptosis in breast cancer cells.